Amazonian Metakaolin Reactivity for Geopolymer Synthesis - Ruy A. Sá Ribeiro; Marilene G. Sá Ribeiro; Gregory P. Kutyla; Waltraud M. Kriven (Advances in Materials Science and Engineering)
To determine the viability of using a local resource for geopolymer synthesis, geopolymers were synthesized using metakaolin made from clay mined in the Amazonian region of Brazil. Samples were made with mixed potassium-sodium and pure sodium metakaolin-based geopolymer. Samples were also made using commercial metakaolin (CMK) from BASF, Inc. as a comparison to the Amazonian metakaolin (AMK). Scanning electron microscopy was used to investigate the microstructure of the materials. X-ray diffraction was able to confirm the formation of geopolymer. The mechanical properties of AMK material were nearly equivalent to those based on CMK. Neither CMK nor AMK reacted completely, although samples made with CMK showed less unreacted material. By increasing the mixing intensity and duration, the amount of residual unreacted material was substantially reduced, and mechanical properties were improved.